Graphene oxide slurry, reduced graphene oxide film and graphene micro-nano cavity superconducting film
By controlling the degree of oxidation and particle size of graphene oxide, and combining specific solvents and additives, the process is optimized to form an ordered reduced graphene oxide film, which solves the problems of insufficient thermal conductivity and bending resistance in the existing technology, and achieves efficient and lightweight heat dissipation.
Patent Information
- Application Number
- CN202411092769.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-11-21
AI Technical Summary
Existing technologies are insufficient to effectively improve the thermal conductivity and bending resistance of reduced graphene oxide thermal conductive films, thus failing to meet the lightweight heat dissipation requirements of electronic devices.
By controlling the degree of oxidation and particle size of graphene oxide, and combining specific solvents and additives, the coating, drying, heat treatment and calendering processes are optimized to form a reduced graphene oxide film with an ordered arrangement.
It significantly improves the thermal conductivity and bending resistance of reduced graphene oxide films, ensuring efficient heat dissipation in electronic devices while maintaining good flexibility and bendability.
Smart Images

Figure CN120987308A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of graphene preparation, in particular to an oxidized graphene slurry and a reduced oxidized graphene film. BACKGROUND
[0002] With the development trend of lightweight electronic devices, traditional VC, fan and other heat dissipation means cannot meet the high-flow heat dissipation demand of electronic components, and it is urgent to find a lightweight heat dissipation material with excellent heat conduction performance. Graphene is currently the material with the highest theoretical heat conduction coefficient, and the preparation of a reduced oxidized graphene heat conduction film on the market usually involves homogenizing, defoaming, coating into an original film, and then carbonizing and graphitizing to obtain the film. In the preparation process, multiple factors such as precursor parameters, precursor selection, preparation process and heat treatment conditions will affect the heat conduction coefficient and other properties of the graphene heat conduction film. SUMMARY
[0003] Based on the above reasons, the inventors have researched precursor parameters, precursor selection, preparation process and heat treatment conditions to improve the heat conduction coefficient of the prepared reduced oxidized graphene heat conduction film.
[0004] In a first aspect, the application provides an oxidized graphene slurry which can be used as a raw material for a reduced oxidized graphene heat conduction film. The slurry comprises: oxidized graphene and a solvent. The oxidized graphene is obtained by homogenizing an oxidized graphene cake and then defoaming. The oxygen content of the oxidized graphene is greater than or equal to 25%, and the mass fraction of the oxidized graphene in the oxidized graphene slurry is 3%-8%. Typically but not limitedly, the oxygen content of the oxidized graphene is 25.0%, 25.50%, 26.0%, 26.5%, 27.0%, 27.5%, 28.0%, 28.56%, 29.0%, 32.87%, 33.86%, 35.0%, 40.0%, 45.0%, 50.0%, 60.0%, 70.0% or 80.0%, and the mass fraction of the oxidized graphene in the oxidized graphene slurry is 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%.
[0005] The oxygen content and solid content of the oxidized graphene are important factors affecting its self-assembly arrangement. The surface of the oxidized graphene contains carboxyl, hydroxyl and epoxy groups and other oxygen-containing functional groups. The presence of these oxygen-containing functional groups makes the oxidized graphene have good dispersibility in water. The realization of self-assembly of the oxidized graphene usually requires removal or partial removal of these functional groups, and new covalent bonds are formed at the fracture of the oxygen-containing functional groups.
[0006] The number of graphene oxide functional groups has a significant impact on its self-assembly behavior: if the oxygen content of graphene oxide is too low, specifically, if the oxygen content is < 25%, the graphene oxide sheet only carries a small amount of oxygen-containing functional groups, and the self-assembly process is difficult to achieve chemical bonding between adjacent graphene oxide sheets, that is, the self-assembly performance of graphene oxide is not good, and a large number of suspended (or hole) defects are introduced between the graphene oxide sheet gaps, and the thermal conductivity is reduced. The mass fraction of graphene oxide in the graphene oxide slurry is 3%-8%, which can ensure that it is in a uniform dispersed state in the slurry.
[0007] In a further aspect, the oxidation degree and particle size of graphene oxide follow the following rules: When the C-O peak in the XPS test of graphene oxide is ≥ the C-C peak, the median particle size is ≤ 1 μm; and / or, when the C-O peak in the XPS test of graphene oxide is < the C-C peak, 1 μm < the median particle size ≤ 10 μm.
[0008] That is, the smaller the graphene oxide sheet diameter, the higher the thermal conductivity of the film, which applies to graphene oxide with high oxidation degree (C-O peak > C-C peak in XPS spectrum), which is due to the fact that after the graphene oxide sheet diameter is reduced, the graphene oxide fragments still carry a certain amount of oxygen-containing functional groups, the self-assembly process can achieve chemical bonding between adjacent graphene oxide sheets, and the graphene oxide in the aqueous phase is mainly in three conformations of flat, wrinkled, twisted, and folded, and the latter three conformations are not conducive to the macroscopic self-assembly of graphene oxide film (the wrinkled, twisted, and folded conformations are easy to form microcapsule structures). After the graphene oxide sheet diameter is reduced by homogeneous regulation, the proportion of the latter three conformations of the graphene oxide sheet layer is reduced, the proportion of the flat conformation of the graphene oxide sheet layer is increased, and the graphene oxide sheet of the coated graphene oxide film exists in the flat conformation (similar to liquid crystal). This is conducive to self-assembly and improves the thermal conductivity. Specifically, for graphene oxide with high oxidation degree (C-O peak > C-C peak in XPS spectrum), the median particle size should be regulated to ≤ 1 μm; On the contrary, the larger the graphene oxide sheet diameter, the higher the thermal conductivity of the film, which applies to graphene oxide with low oxidation degree (C-O peak < C-C peak in XPS spectrum), which is due to the fact that after the graphene oxide sheet diameter is reduced, the graphene oxide fragments only carry a small amount of oxygen-containing functional groups or do not carry oxygen-containing functional groups, and it is difficult to achieve perfect chemical bonding between adjacent graphene oxide sheets in the self-assembly process. A large number of suspended (or hole) defects are introduced between the graphene oxide fragment gaps, and the SP 2The hybrid long-range order is destroyed, and the phonon transmission process is scattered a lot at the edge defects of graphene fragments, and the thermal conductivity is reduced; therefore, the graphene oxide with low oxidation degree (XPS spectrum C-O peak < C-C peak) needs to ensure a certain size of the flake size (1 μm < median particle size ≤ 10 μm) to reduce the introduction of defects and improve the thermal conductivity. Preferably, when the C-O peak < C-C peak in the XPS test of the graphene oxide, 1.5 μm ≤ median particle size ≤ 10 μm.
[0009] In a further scheme, the solvent in the graphene oxide slurry includes one or more of deionized water, ammonia water, DMF, NMP, ethanol and isopropanol.
[0010] The graphene oxide slurry formed by combining any one or more of the above schemes is coated into a raw film, dried, heat treated and calendered to obtain a reduced graphene oxide film. Due to the more ordered arrangement and more suitable coating state in the self-assembly process, the thermal conductivity of the reduced graphene oxide film is improved, and the horizontal thermal diffusivity of the reduced graphene oxide film is ≥ 800 mm 2 / s.
[0011] In a further scheme, the graphene oxide slurry further includes one or more of carbon nanotubes, carbon fibers, reduced graphene oxide powder and CVD graphene powder.
[0012] The graphene oxide slurry of this scheme or the combination of this scheme and any one or more of the above schemes is coated into a raw film, dried, heat treated and calendered to obtain a reduced graphene oxide film. The reduced graphene oxide film has better bending resistance, and specifically, the bending resistance of the reduced graphene oxide film is ≥ 400,000 times.
[0013] The carbon nanotubes, carbon fibers, reduced graphene oxide powder and CVD graphene powder have flexibility. For the carbon nanotubes, the carbon-carbon double bonds of the carbon nanotubes can cause the carbon nanotubes to have strong flexibility. When the carbon nanotubes are subjected to bending or tensile stress, the carbon-carbon double bonds in the carbon nanotubes are broken to form a new form, so that the carbon nanotubes become more flexible and bendable. For the carbon fibers, the flexibility of the carbon fibers is mainly due to the preferred orientation of the graphite crystalline structure along the fiber axis. This structural characteristic makes the carbon fibers have high strength and modulus along the fiber axis. For the reduced graphene oxide powder and CVD graphene powder, they have a crumpled morphology in the microscopic state. When the material is subjected to external tensile or bending stress, the graphene sheets can unfold to adapt to the deformation caused by external force and provide sufficient degrees of freedom for complex deformation such as bending. The above precursors are added to the graphene oxide slurry, and finally the bending resistance of the reduced graphene oxide film obtained by post-processing is improved.
[0014] Further, the graphite oxide slurry also includes one or more of the broken reduced graphene oxide film fragments and the broken graphene superconducting film fragments. The addition of the heat-conductive material in the form of a heat-conductive filler to the graphene oxide slurry weakens the anisotropic performance of the graphene oxide slurry during the self-assembly process and increases the longitudinal heat conduction channel.
[0015] The graphene oxide slurry formed by the scheme or the combination of the scheme with any one or more of the above schemes is coated into a raw film, dried, heat treated, and calendered to obtain a reduced graphene oxide film, which has a better longitudinal thermal conductivity coefficient. Specifically, the reduced graphene oxide film has a vertical thermal diffusivity of ≥ 10 mm 2 / s.
[0016] The graphene oxide slurry formed by the combination of any one or more of the above schemes is coated into a raw film, foamed, dried, heat treated, and calendered to obtain a graphene micro-nano cavity superconducting film. The graphene micro-nano cavity superconducting film includes micro-nano cavities with a size of 1 μm to 150 μm. Due to the existence of the micro-nano cavities, the graphene micro-nano cavity superconducting film can quickly disperse stress when subjected to external compression stress, is compressed without damaging the film material structure, and rebounds when no longer subjected to external force.
[0017] Typically but not limitedly, the foaming in the preparation process of the graphene micro-nano cavity superconducting film is foaming reduction by immersing the raw film in at least one of hydrazine hydrate, sodium borohydride, dimethylhydrazine, and thiourea.
[0018] In the preparation process of the reduced graphene oxide film or the graphene micro-nano cavity superconducting film described in any one of the above schemes, the graphene oxide slurry should be placed for a time of < 6 h before being coated into a raw film. If the defoaming time of the graphene oxide slurry is > 6 h, partial self-assembly occurs in the slurry state before coating, the slurry as a whole becomes sticky and thick, and the smoothness in the subsequent coating process and the uniformity when being coated into a raw film are affected.
[0019] In the preparation process of the reduced graphene oxide film described in any one of the above schemes, the heat treatment includes a pretreatment process at 150-380 ℃, a carbonization process at 900-1400 ℃, and a graphitization process at 2000-3300 ℃. The segmented heat treatment can avoid film material bubbling, delamination, fracture, or burning caused by rapid heat reduction of the film. In the pretreatment stage, water and a small amount of oxygen-containing functional groups are removed. In the carbonization stage, most of the oxygen-containing functional groups are removed. In the graphitization stage, the oxygen-containing functional groups are substantially completely removed, and various defects are repaired, and the intrinsic thermal conductivity of graphene is improved.
[0020] Compared with the prior art, the present application has the following beneficial effects: 1. By adjusting the oxidation degree, particle size parameters and the selection of different precursors of graphene oxide in graphene oxide slurry, the thermal conductivity and bending resistance of the reduced graphene oxide film or graphene micro-nano cavity superconducting film formed by coating and other post-processing are affected.
[0021] 2. According to the C-O peak intensity and C-C peak intensity in the C1s scanning spectrum of the XPS of the graphene oxide raw material, it can be judged whether the graphene oxide precursor slurry is suitable for small flake size parameters or large flake size parameters, thereby avoiding a large number of trial and error on different types of graphene oxide cakes, greatly saving manpower and resources and improving production efficiency. BRIEF DESCRIPTION OF DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings needed in the embodiment description will be briefly introduced. Obviously, the drawings in the following description are some embodiments of the present application, and other drawings can also be obtained by those skilled in the art without creative labor.
[0023] Figure 1 XPS characterization test spectrum of A52 type graphene oxide cake used in Example 1; Figure 2 Thermal diffusivity test graph of the horizontal direction of the reduced graphene oxide film of Example 1; Figure 3 XPS characterization test spectrum of graphene oxide cake used in Example 2; Figure 4 Thermal diffusivity test graph of the horizontal direction of the reduced graphene oxide film of Example 2; Figure 5 XPS characterization test spectrum of graphene oxide cake used in Example 3; Figure 6 Thermal diffusivity test graph of the horizontal direction of the reduced graphene oxide film of Example 3; Figure 7 XPS characterization test spectrum of graphene oxide cake used in Example 4; Figure 8 Thermal diffusivity test graph of the horizontal direction of the reduced graphene oxide film of Example 4; Figure 9 Thermal diffusivity test graph of the horizontal direction of the reduced graphene oxide film of Example 5; Figure 10 State graph of the reduced graphene oxide film of Example 6 after 400,000 times of bending resistance test; Figure 11 SEM graph of the graphene micro-nano cavity superconducting film of Example 13. DETAILED DESCRIPTION
[0024] The following detailed description of examples of the application references the accompanying drawings, which form a part of the description. The drawings are illustrative of examples of the application and are not therefore to be considered limiting in scope. The application is described and explained with additional specificity and detail through the use of the accompanying drawings in which:
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used in the description herein is for describing particular embodiments only and is not intended to be limiting upon the scope of the application; and the use herein of the terms "and / or" includes a set of one or more associated listed items.
[0026] Unless otherwise indicated, conventional methods and techniques of molecular biology, microbiology, recombinant DNA, immunology, and protein purification may be used, for example, as described in Sambrook et al., Molecular Cloning: A Laboratory Manual, 3rd Ed., Cold Spring Harbor Press, Cold Spring Harbor, N.Y. (2001); Sambrook and Russell, Molecular Cloning: A Laboratory Manual, 3rd Ed., Cold Spring Harbor Press, Cold Spring Harbor, N.Y. (2001); and Ausubel et al., Short Protocols in Molecular Biology: A Compendium of Techniques, 4th Ed., John Wiley & Sons, Inc., New York (1999), the contents of which are hereby incorporated by reference.
[0027] To make the technical problems, technical solutions and advantages of the present application clearer, the following will be described in detail with reference to the accompanying drawings and specific examples.
[0028] The reduced graphene oxide film is used as a light-weight, excellent heat-conducting heat-dissipating material, and is widely used in the 3C field, the new energy field, etc. How to stably control the heat-conducting performance, bending resistance and other performances of the reduced graphene oxide film is the core problem that customers are concerned about in the product application process.
[0029] To this end, the applicant has made a lot of attempts in the research and development process, including adjustment of heat treatment temperature and improvement of coating process, but the effect still cannot meet the demand.
[0030] Meanwhile, the applicant also finds through a large number of tests and data collection that graphene thermal conductive film precursor graphene oxide is mainly in four conformations of laying, folding, winding and folding in the aqueous phase, and the key to improving the thermal conductivity of the reduced graphene oxide thermal conductive film lies in reducing the defects of the graphene thermal conductive film, improving the SP 2 of the carbon six-membered ring structure of the graphene thermal conductive film, reducing the long-range order degree and crystallinity of the hybrid, and reducing the internal microcapsule structure, void and other adverse heat conduction conformations. The three conformations of folding, winding and folding are prone to form a large number of microcapsule and void structures in the self-assembly process of the graphene oxide coating film, which is not conducive to the improvement of the self-assembly and thermal conductivity. The applicant finds that the accurate control of the particle size of graphene oxide combined with the oxidation degree of graphene oxide can reduce the proportion of the last three conformations, increase the laying conformation, reduce the microcapsule and void structure of the graphene oxide sheet in the coating film, and thus improve the thermal conductivity of the reduced graphene oxide film.
[0031] The applicant also finds through repeated verification and analysis that the control of the precursor type in the graphene oxide slurry can control the bending resistance of the reduced graphene oxide film.
[0032] The following are specific embodiments and comparative examples of the present application, in which: The test method of the solid content of the graphene oxide cake is as follows: first, weigh the mass of the stripping culture dish and record it as m1; put the wet cake to be tested into the stripping culture dish and record it as m2, wherein the mass of the wet cake is m2-m1; transfer the culture dish containing the wet cake to a 40-90 DEG C air oven and dry it, and record the mass of the cake + stripping culture dish as m3; at this time, the mass of the cake no longer changes, that is, the moisture in the wet cake is all ash, and the cake is a dry cake; the solid content of the cake is calculated as (m3-m1) / (m2-m1), and the data is recorded in percentage form; in order to ensure the accuracy of the data, 3-5 groups of cakes are measured, and the average value is taken; in order to reduce the error of the data, the mass of a wet cake is ≥3g, and 10-20g per portion is better; in order to ensure the evaporation of moisture during the drying process of the cake, the cake should be in the form of small particles or flat and thin as much as possible, such as flattening and sieving.
[0033] The XPS test method is as follows: an XPS tester with model ESCA lab 250 is used, the sample is tested in an energy analysis mode with a base pressure of 3x10 -8 Pa, and an X-ray with A1 Ka 1486.8eV is used as the excitation source to test the chemical composition of the sample.
[0034] The test method of the oxygen content of the cake is to use XPS test characterization.
[0035] The median particle size test method is to use a laser particle size analyzer for testing.
[0036] The test method for the horizontal thermal diffusivity is as described in standard QGDMR 04-2023, "Laser flash method for testing thermal conductivity".
[0037] The method for testing the vertical thermal diffusivity is as described in standard GB / T 22588-2008, "Measuring Thermal Diffusivity or Thermal Conductivity by Flash Method".
[0038] The bending resistance test method is as follows: the reduced graphene oxide film is cut into strips with a specification of 110*25mm, and the strips are placed on the FPC bending tester and tested at a test angle of 90° on one side and a test speed of 120 times / min. Example 1
[0039] A graphene oxide slurry: The graphene oxide cake purchased from Yuntian Morui was homogenized and defoamed. Its oxygen content was 35.0%, and its solid content (i.e., the mass fraction of graphene oxide in the graphene oxide slurry) was 4.5%. The solvent was deionized water. The measured XPS spectrum showed that its CO peak intensity was greater than that of CC peak intensity, and its particle size D50 control value was 0.476 μm.
[0040] The preparation method of the graphene oxide slurry in Example 1 is as follows: S1. Purchase A52 type graphene oxide cake from Yuntian Morui. Take 50g and flatten it in a glass petri dish. Dry it in a 78°C forced-air oven until the mass no longer changes and calculate the solid content of the graphene oxide cake to be 48.90%. Take another 50g of A52-1 type graphene oxide cake and pass it through a 100-mesh sieve to obtain a fine graphene oxide cake. Dry it in a 78°C forced-air oven and then grind it through a 150-mesh sieve to obtain graphene oxide powder. Perform XPS characterization tests on the obtained graphene oxide powder to obtain... Figure 1 The XPS plot shown; S2. Using deionized water, A52 type graphene oxide cake was prepared into an aqueous slurry with a solid content of 4.5%. The graphene oxide dispersion slurry was obtained by stirring and dispersing it using a planetary mixer. The parameters of the planetary mixer were set as follows: stirring speed 100 r / min, dispersion speed 3000 r / min, and working time 3 h. The particle size of the graphene oxide dispersion slurry was controlled by a homogenizer, and the particle size D50 control value was 0.476 μm. After homogenization, the graphene oxide slurry was subjected to vacuum degassing treatment to obtain the target graphene oxide slurry.
[0041] A reduced graphene oxide film: The target graphene oxide slurry was coated into a film, dried, heat-treated, and calendered. Its horizontal thermal diffusivity was measured as follows: Figure 2 As shown, it is 914.77mm.2 / s, the vertical thermal diffusivity is 5.85mm. 2 / s.
[0042] The method for preparing the reduced graphene oxide film in Example 1 is as follows: The target graphene oxide slurry was left to stand for 0 hours, then coated with a 5 mm thick slurry and dried in a low humidity atmosphere to obtain the original film. The original film was then pretreated at 260℃ for 1 hour, carbonized at 1200℃ for 1 hour in a nitrogen atmosphere, and graphitized at 2900℃ for 1 hour in an argon atmosphere. Finally, the target reduced graphene oxide film was obtained by flat pressing. Example 2
[0043] The difference between this embodiment and Example 1 is that in step S1, another batch of graphene oxide cake is used instead of the graphene oxide cake used in Example 1. All other steps and process parameters are the same as in Example 1. The purpose is to explore the effects of graphene raw materials with different oxidation degrees and different controlled median particle sizes on the thermal conductivity of graphene thermal conductive film.
[0044] The test results showed: Graphene oxide slurry: Its oxygen content is 32.87%, solid content (i.e., the mass fraction of graphene oxide in the graphene oxide slurry) is 4.5%, the solvent is deionized water, and the measured XPS spectrum is as follows. Figure 3 As shown, its CO peak intensity is greater than its CC peak intensity, and its particle size D50 control value is 0.528 μm.
[0045] Reduced graphene oxide film: Horizontal thermal diffusivity results are as follows Figure 4 As shown, it is 861.24mm. 2 / s, the vertical thermal diffusivity is 5.42mm. 2 / s. Example 3
[0046] The difference between this embodiment and Example 1 is that in step S1, another batch of graphene oxide cake is used instead of the graphene oxide cake used in Example 1. All other steps and process parameters are the same as in Example 1. The purpose is to explore the effects of graphene raw materials with different oxidation degrees and different controlled median particle sizes on the thermal conductivity of graphene thermal conductive film.
[0047] The test results showed: Graphene oxide slurry: Its oxygen content is 33.86%, solid content (i.e., the mass fraction of graphene oxide in the graphene oxide slurry) is 4.5%, the solvent is deionized water, and the measured XPS spectrum is as follows. Figure 5 As shown, the CO peak intensity is similar to the CC peak intensity, but the CO peak is slightly higher than the CC peak, and its particle size D50 control value is 0.799 μm.
[0048] Reduced graphene oxide film: Horizontal thermal diffusivity results are as follows Figure 6 As shown, it is 834.41mm. 2 / s, the vertical thermal diffusivity is 5.23mm. 2 / s. Example 4
[0049] The difference between this embodiment and Example 1 is that in step S1, another batch of graphene oxide cake is used instead of the graphene oxide cake used in Example 1. All other steps and process parameters are the same as in Example 1. The purpose is to explore the effects of graphene raw materials with different oxidation degrees and different controlled median particle sizes on the thermal conductivity of graphene thermal conductive film.
[0050] The test results showed: Graphene oxide slurry: Its oxygen content is 28.56%, solid content (i.e., the mass fraction of graphene oxide in the graphene oxide slurry) is 4.5%, the solvent is deionized water, and the measured XPS spectrum is as follows. Figure 7 As shown, its CO peak intensity is significantly weaker than its CC peak intensity, and its particle size D50 control value is 4.177 μm.
[0051] Reduced graphene oxide film: Horizontal thermal diffusivity results are as follows Figure 8 As shown, it is 858.41mm. 2 / s, the vertical thermal diffusivity is 6.20mm. 2 / s. Example 5
[0052] The difference between this embodiment and Example 4 is that the particle size of the graphene oxide cake dispersion slurry is controlled to D50=1.557μm. All other steps and process parameters are the same as in Example 4. The purpose is to explore the effect of particle size control on the thermal conductivity of graphene thermal conductive film.
[0053] The test results showed: Graphene oxide slurry: Its oxygen content is 28.56%, solid content (i.e., the mass fraction of graphene oxide in the graphene oxide slurry) is 4.5%, the solvent is deionized water, and the measured XPS spectrum is as follows. Figure 8 The results show that its CO peak intensity is significantly weaker than its CC peak intensity, and its particle size D50 control value is 1.557 μm.
[0054] Reduced graphene oxide film: Horizontal thermal diffusivity results are as follows Figure 9 As shown, 865.19 is in mm. 2 / s, the vertical thermal diffusivity is 5.98mm. 2 / s. Examples 6-10
[0055] The difference between the present examples and Example 1 is that in step S2, the A52 model graphene oxide material cake is respectively prepared into a water-based slurry with a solid content of 4.5% with carbon nanotubes, carbon fibers, reduced graphene oxide powder, CVD graphene powder, and the particle size D50 control value is 0.459 μm, 0.382 μm, 0.783 μm, 0.891 μm respectively, and the remaining steps are consistent with Example 1.
[0056] Test results are as follows: The oxygen content of the graphene oxide raw material is 35.0%, the solid content (i.e. the mass fraction of graphene oxide in graphene oxide slurry) is 4.5%, the solvent is deionized water, and the measured XPS spectrum shows that the C-O peak intensity > C-C peak intensity, and the particle size D50 control value is 0.459 μm, 0.382 μm, 0.783 μm, 0.891 μm respectively.
[0057] The horizontal thermal diffusivity of the reduced graphene oxide film is 824.77 mm 2 / s, 832.53 mm 2 / s, 879.23 mm 2 / s, 882.59 mm 2 / s, 4.07 mm 2 / s, 4.21 mm 2 / s, 4.94 mm 2 / s, 5.19 mm 2 / s, all through the bending resistance test of 1 million times, wherein, the state of the film material after the bending resistance test in Example 6 is as shown in Figure 10 , and the sample is measured to 4 million times without delamination, bulging or fracture phenomenon. Examples 10-11
[0058] The difference between the present examples and Example 1 is that in step S2, the A52 model graphene oxide material cake is respectively prepared into a water-based slurry with a solid content of 4.5% with broken reduced graphene oxide film fragments and broken graphene superconducting film fragments, and the particle size D50 control value is 0.658 μm, 0.635 μm respectively, and the remaining steps are consistent with Example 1.
[0059] Test results are as follows: The oxygen content of the graphene oxide raw material is 35.0%, the solid content (i.e. the mass fraction of graphene oxide in graphene oxide slurry) is 4.5%, the solvent is deionized water, and the measured XPS spectrum shows that the C-O peak intensity > C-C peak intensity, and the particle size D50 control value is 0.658 μm, 0.635 μm respectively.
[0060] Reduced graphene oxide film: the horizontal thermal diffusivity coefficient of which was tested to be 824.21 mm 2 / s, and the vertical thermal diffusivity coefficient was 12.07 mm 2 / s, respectively. 2 / s, and 11.34 mm 2 / s, respectively. Example 12
[0061] The difference between this example and Example 1 is that the target graphene oxide slurry is allowed to stand for 6 hours before the subsequent steps of coating the original film, drying, heat treatment and calendering are performed, and the rest of the steps remain the same as in Example 1. The purpose is to explore the influence of slurry standing on the thermal conductivity of graphene thermal conductivity film. The results show that the horizontal thermal diffusivity coefficient of the obtained graphene thermal conductivity film is 803.21 mm 2 / s, which is still higher than 800 mm 2 / s, but lower than Example 1. This is due to the self-assembly during the standing of the slurry, which thickens and affects the uniformity in the subsequent coating process, thereby affecting the thermal conductivity of the reduced graphene oxide film. Example 13
[0062] The difference between this example and Example 1 is that the graphene micro-nano cavity superconducting film is prepared in this example. The graphene oxide slurry prepared in steps S1 and S2 is consistent with Example 1.
[0063] The preparation method of the graphene micro-nano cavity superconducting film in this example is as follows: The target graphene oxide slurry is coated immediately after standing for 0 hours to a thickness of 5 mm and dried in a low humidity atmosphere to obtain an original film. The original film is reacted with hydrazine hydrate, a foaming composition, to obtain a wet graphene foaming film. Then it is dried in a drying oven, and then subjected to 1200°C carbonization treatment for 1 hour under nitrogen atmosphere, and 2900°C graphitization treatment for 1 hour under argon atmosphere. Finally, the target graphene micro-nano cavity superconducting film is obtained by flat pressing.
[0064] The horizontal thermal diffusivity coefficient of which was tested to be 892.36 mm 2 / s.
[0065] The graphene micro-nano cavity superconducting film is observed by SEM, and it is found that the graphene micro-nano cavity superconducting film has micro-nano pores inside. The size of the pores varies randomly due to chemical reduction foaming, and is generally 1 μm to 150 μm. Comparative Example 1
[0066] The difference between this comparative example and Example 1 is that in step S2, the particle size of the graphene oxide cake dispersion slurry is controlled to D50 = 1.254 μm. All other steps and process parameters are the same as in Example 1. The purpose is to investigate the effect of non-optimal particle size control on the thermal conductivity of the graphene thermal conductive film. The results show that the horizontal thermal diffusivity of the graphene oxide thermal conductive film obtained in Comparative Example 1 is 694.71 mm. 2 / s, which is much lower than in Example 1, is attributed to the fact that there are still many graphene oxide sheet conformations such as wrinkles, overlaps, and entanglements that are detrimental to thermal conductivity in the graphene oxide film at this particle size. Comparative Example 2
[0067] The difference between this comparative example and Example 2 is that in step S2, the particle size of the graphene oxide cake dispersion slurry is controlled to D50 = 1.153 μm. All other steps and process parameters are the same as in Example 2. The purpose is to investigate the effect of non-optimal particle size control on the thermal conductivity of the graphene thermal conductive film. The results show that the horizontal thermal diffusivity of the graphene oxide thermal conductive film obtained in Comparative Example 2 is 698.07 mm. 2 / s, which is much lower than in Example 2, is attributed to the fact that there are still many graphene oxide sheet conformations such as wrinkles, overlaps, and entanglements that are detrimental to thermal conductivity in the graphene oxide film at this particle size. Comparative Example 3
[0068] The difference between this comparative example and Example 3 is that the particle size of the graphene oxide cake dispersion slurry was controlled to D50 = 1.839 μm in step S2. All other steps and process parameters were the same as in Example 3. The purpose was to investigate the effect of non-optimal particle size control on the thermal conductivity of the graphene thermal conductive film. The results showed that the horizontal thermal diffusivity of the graphene oxide thermal conductive film obtained in Comparative Example 3 was 701.33 mm. 2 / s, which is much lower than in Example 3, is attributed to the fact that there are still many graphene oxide sheet conformations such as wrinkles, overlaps, and entanglements that are detrimental to thermal conductivity in the graphene oxide film at this particle size. Comparative Example 4
[0069] The difference between this comparative example and Example 4 is that the particle size of the graphene oxide cake dispersion slurry was controlled to D50 = 0.420 μm in step S2. All other steps and process parameters were the same as in Example 4. The purpose was to investigate the effect of non-optimal particle size control on the thermal conductivity of the graphene thermal conductive film. The results showed that the horizontal thermal diffusivity of the graphene oxide thermal conductive film obtained in Comparative Example 4 was 645.23 mm. 2 / s, which is much lower than that of Example 4, due to the fact that the graphene oxide film at this particle size has a large number of graphene oxide fragments that do not carry oxygen-containing groups and cannot participate in self-assembly, resulting in a large number of edge defects, which cannot be repaired during the graphitization stage, resulting in a low thermal diffusion coefficient of the obtained graphene thermal conductive film. Comparative Example 5
[0070] The difference between this comparative example and Example 4 is that the particle size of the graphene oxide cake dispersion slurry in step S2 is controlled to D50 = 11.761 μm, and the other steps and process parameters are the same as those of Example 4. The purpose is to explore the influence of non-optimal particle size control on the thermal conductivity of graphene thermal conductive film. The results show that the thermal horizontal direction diffusion coefficient of the graphene thermal conductive film obtained in Comparative Example 5 is 686.9 mm 2 / s, which is much lower than that of Example 4, due to the fact that the graphene oxide film at this particle size has a large number of graphene oxide fragments that do not carry oxygen-containing groups and cannot participate in self-assembly, resulting in a large number of edge defects, which cannot be repaired during the graphitization stage, resulting in a low thermal diffusion coefficient of the obtained graphene thermal conductive film. Comparative Example 6
[0071] The difference between this comparative example and Example 1 is that the reduced graphene oxide film is directly graphitized at 2900℃ during the preparation of the reduced graphene oxide film. Finally, due to the simultaneous release of a large amount of gas during the heat treatment of the reduced graphene oxide film, the film material is directly broken and burned. Comparative Example 7
[0072] The difference between this comparative example and Example 13 is that the particle size of the graphene oxide cake dispersion slurry in step S2 is controlled to D50 = 1.153 μm, and the other steps and process parameters are the same as those of Example 13. The purpose is to explore the influence of non-optimal particle size control on the thermal conductivity of graphene micro-nano cavity superconducting film. The results show that the thermal horizontal direction diffusion coefficient of the graphene micro-nano cavity superconducting film obtained in Comparative Example 7 is 654.19 mm 2 / s, which is lower than that of Example 13.
[0073] In the above examples, the description of each example has its own focus, and the parts not described in detail in a certain example can be referred to the relevant description of other examples.
[0074] The above is a specific embodiment of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present application, which should be covered within the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. An oxidized graphene slurry, characterized by, The graphene oxide and the solvent are characterized in that the graphene oxide is obtained by defoaming after homogenizing a graphene oxide cake, the oxygen content of the graphene oxide is greater than or equal to 25%, and the mass fraction of the graphene oxide in the graphene oxide slurry is 3%-8%.
2. A graphene oxide slurry as claimed in claim 1, characterized in that, The oxidation degree and the particle size of the graphene oxide follow the following rules: When the C-O peak is greater than the C-C peak in the XPS test of the graphene oxide, the median particle size is less than or equal to 1 μm; When the C-O peak is less than the C-C peak in the XPS test of the graphene oxide, the median particle size is greater than 1 μm and less than or equal to 10 μm, preferably, the median particle size is greater than 1.5 μm and less than or equal to 10 μm.
3. The graphene oxide slurry of claim 1, wherein, The solvent includes one or more of deionized water, ammonia, DMF, NMP, ethanol and isopropanol.
4. The graphene oxide slurry of claim 1, wherein, The graphene oxide slurry further includes one or more of carbon nanotubes, carbon fibers, reduced graphene oxide powder and CVD graphene powder.
5. The graphene oxide slurry of claim 1, wherein, The graphene oxide slurry further includes one or more of broken reduced graphene oxide film fragments and broken graphene superconducting film fragments.
6. A reduced graphene oxide film, characterized by, The graphene oxide slurry according to any one of claims 1 to 3 is coated into a raw film, dried, heat treated, and calendered to obtain a reduced graphene oxide film, wherein the thermal diffusion coefficient of the reduced graphene oxide film in the horizontal direction is ≥ 800 mm 2 / s.
7. A reduced graphene oxide film, characterized by, The graphene oxide slurry of claim 4 is coated into a raw film, dried, heat treated, and calendered to obtain the reduced graphene oxide film, and the reduced graphene oxide film has a folding resistance of greater than or equal to 400,000 times.
8. A reduced graphene oxide film, characterized by, The graphene oxide slurry as claimed in claim 5 is coated into a raw film, dried, heat treated, and calendered to obtain the reduced graphene oxide film, and the thermal diffusion coefficient of the reduced graphene oxide film in the vertical direction is ≥ 10 mm 2 / s.
9. A graphene microcavity superconducting film, characterized in that, The graphene oxide slurry of any one of claims 1-3 is coated into a raw film, foamed, dried, heat treated, and calendered to obtain the graphene micro-nano cavity superconducting film, and the graphene micro-nano cavity superconducting film includes micro-nano cavities with a size of 1 μm-150 μm.
10. The graphene micro-nano-cavity superconducting film according to claim 9, wherein, The foaming is foaming reduction by immersing the raw film in at least one of hydrazine hydrate, sodium borohydride, dimethylhydrazine and thiourea.
11. A reduced graphene oxide graphene film according to any one of claims 6 to 8 or a graphene microcavity superconductor film according to any one of claims 9 to 10, wherein, The graphene oxide slurry is coated into a raw film, and the standing time is less than 6 hours.
12. A reduced graphene oxide film as claimed in any one of claims 6 to 8 characterised in that, The heat treatment includes a pretreatment process at 150-380 ℃, a carbonization process at 900-1400 ℃, and a graphitization process at 2000-3300 ℃.